Improving QoS for Real-time Traffic using Multiple Low Latency Queueing Scheduling Mechanisms (University of Khartoum Engineering Journal, 2022)
In this work, a Multiple Low Latency Queuing scheduling mechanism model is developed to improve the QoS performance for real time and critical mission data traffic in LTE mobile networks. The main objective of this model is to achieve minimum delay and improve the QoS for real time applications (like Live Video and Voice over LTE). In addition, issues likestarvation of lower priority queues and bandwidth allocation are addressed. The model is composed of four components, first, classifier to classify the incoming traffic in router interface. Second, four Class Based Weighted Fair Queues (CBWFQ) scheduling mechanisms, with activation of strict priority feature in the first two queues. Third, two separate rate limiters (policers), one for each strict priority queue. Two scenarios are designed and simulated using Optimized Network Engineering Tool (OPNET). The results show that, in the case of Multiple Low Latency Queuing scheduling mechanism model, the real time traffic suffers less delay compared to the case of existing scheduling mechanisms like (Custom Queuing, Priory Queuing, CBWFQ and Low Latency Queuing). On the other hand, the model also addressed the starvation of lower-priority queuesproblem.